AI Tools in Marketing Research: Integration, Evaluation and Recommendations for Romanian Firms - Epure, Manuela (Journal of Economic Development, Environment and People, 2025)
The paper aims to explore AI adoption in marketing at the firm level. It is relevant to note that AI–driven solutions have flourished in the field of marketing, from developing marketing content to identifying consumer behaviour patterns to decision-making. Subsequently, AI-driven marketing solutions are crucial in empowering businesses to transition from conventional marketing methodologies to sophisticated, data-centric strategies. The paper presents the advantages and disadvantages of adopting AI tools in marketing, emphasising the importance of shifting to AI-driven solutions to support long-term strategies, with the expectation of significant benefits in terms of ROI. Additionally, marketers are provided with recommendations on the basic methodological approach to consider when adopting AI. A brief presentation of the current status of AI adoption in marketing activities, showcasing examples of AI-powered tools available for various marketing actions. A dedicated section is devoted to AI tools used in marketing research, given that large-scale data are used to better understand consumers, markets, and competition. Because AI adoption means significant investments and risks to be considered, a methodology of AI implementation is provided as recommendations to Romanian companies